Faith-based pharmaceutical supply chains and their role in African pharmaceutical systems: A qualitative systematic review - Isatu Jalloh; Jill Olivier; Eleanor Beth Whyle (Health for All Nations, 2024)
For the health system to function well, the population must have equitable access to quality, affordable pharmaceutical supplies; however, pharmaceutical systems in Africa are challenged by inadequate funding, drug stock outs and irregular supplies, a shortage of trained pharmacy personnel, and a lack of systems for drug regulation and quality. Faith-based health providers, as private, not-for-profit actors, have long complemented public sector efforts in the supply of pharmaceuticals in Africa. However, the contribution of faith-based health providers in pharmaceutical systems has not been formally studied. This study examines the nature and function of faith-based healthcare providers in improving access to pharmaceutical supplies in Africa. To do so, we conducted an exploratory qualitative systematic review to identify documents that contain information on faith-based involvement in pharmaceutical supply in Africa. The review identified 20 articles for inclusion. These articles were analyzed using thematic, narrative analysis. The analysis revealed a significant evidence gap relating to the contribution of private-not-for-profit, faith-based providers to African pharmaceutical systems. The review suggests that while faith-based drug supply organizations have existed for a long time and contribute significantly to national pharmaceutical systems, there is very little known about the nature of faith-based pharmaceutical providers and how they complement public sector pharmaceutical systems. In many contexts, faith-based involvement in pharmaceutical systems improved access for the general population and increased the supply of pharmaceuticals in national systems. Faith-based drug supply organizations also often provide pharmaceutical supplies to both rural and urban areas, often targeting rural and remote areas particularly. The review also indicates that faith-based drug supply organizations improved access to medicines and related commodities and, despite a lack of regulation in many contexts, have the potential to make a positive contribution to quality assurance of pharmaceuticals. In summary, the analysis confirmed that faith-based involvement in pharmaceutical supply chains contributes to strengthening the national health system by complementing the public pharmaceutical system through improved access to medicines and related commodities in Africa. These conclusions corroborate the need to continually document and acknowledge faith-based healthcare providers' efforts which could guide the formulation of stringent, evidence-based strategies.